2012
DOI: 10.15376/biores.7.2.2260-2271
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Integrated Tempo-Mediated Oxidation and Recycling on the Properties of TMP Fibers

Abstract: In order to improve the properties of thermomechanical pulp (TMP), the influences of the TEMPO (2,2,6,6-tetramethylpiperidyl-1-oxyl radical)-mediated oxidation on recycled TMP properties were investigated, and the impacts of recycling process on TEMPO-mediated oxidized TMP properties were studied as well. The results showed that TEMPOmediated oxidation is an effective way to enhance the recycled TMP inter-fiber bonding dependent properties due to the introduction of carboxylic acid groups onto pulp, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Such chemical derivatization of fiber surfaces can be viewed as a relatively aggressive strategy, compared to relying on adsorption. Carboxylation, leading to higher bonding strength in paper, has been achieved by periodate oxidation (Alince 1975), by carboxymethylation (Ruffini 1966;Lindström and Carlsson 1982;Laine et al 2003;Torgnysdøtter and Wågberg 2003), by ozone treatment (Minor et al 1993), by TEMPO-mediated oxidation (Kitaoka et al 1999;Le Roux et al 2006;Song and Law 2010;Aracri et al 2012;Ma et al 2012), or by enzyme-catalyzed derivatization with various carboxylic acid or aldehyde-containing species (Liu et al 2013). Most of the cited studies showed increased strength of paper prepared from the modified fibers.…”
Section: Carboxylation Of Fiber Surfacesmentioning
confidence: 99%
“…Such chemical derivatization of fiber surfaces can be viewed as a relatively aggressive strategy, compared to relying on adsorption. Carboxylation, leading to higher bonding strength in paper, has been achieved by periodate oxidation (Alince 1975), by carboxymethylation (Ruffini 1966;Lindström and Carlsson 1982;Laine et al 2003;Torgnysdøtter and Wågberg 2003), by ozone treatment (Minor et al 1993), by TEMPO-mediated oxidation (Kitaoka et al 1999;Le Roux et al 2006;Song and Law 2010;Aracri et al 2012;Ma et al 2012), or by enzyme-catalyzed derivatization with various carboxylic acid or aldehyde-containing species (Liu et al 2013). Most of the cited studies showed increased strength of paper prepared from the modified fibers.…”
Section: Carboxylation Of Fiber Surfacesmentioning
confidence: 99%